Effect of gas saturation conditions on the expansion ratio of microcellular poly(lactic acid)/wood-flour composites (eXPRESS Polymer Letters, 2010)
Poly(lactic acid) or PLA and PLA/wood-flour composites were microcellular foamed with CO2 through a batch foaming process. Specifically, the gas saturation pressure and time varied during processing to produce PLA foams with a high expansion ratio. A ten fold expansion ratio resulted in microcellular foamed PLA over unfoamed counterpart. The foaming conditions associated with such a high expansion ratio involved a lower gas saturation pressure up to 2.76 MPa, which corresponds to a critical gas concentration of approximately 9.4%. Beyond this critical value, foam expansion decreased significantly. Investigations also studied the effect of incorporating wood flour on the foamability of the resulting PLA/wood-flour composites. The addition of wood flour into the PLA matrix significantly affected the expansion ratio of PLA/wood-flour composite foams.